PRELIMINARY STUDY OF PARTICLE SIZE MEASUREMENT OF FINE PHOSPHATE ROCKS USING DYNAMIC LIGHT SCATTERING METHOD - AGUS WAHYUDI; SARIMAN SARIMAN; SITI ROCHANI (Indonesian Mining Journal, 2011)
Particle size measurement is an important role in the utilization of phosphate rocks for nanofertilizer. In this study, the phosphate rocks from Wonosari and Ciamis were milled by planetary ball mill (PBM) into submicron size (0.19 μm). Measurements of the submicron size were conducted using a dynamic light scattering (DLS) method, i.e. iluminating. The milled products were also compared to the milled zeolite and bentonite from the same PBM. There is a relationship between the particle milled size and its chemical composition. The correlation is interpreted as the result of different hardness in minerals content.